Pengaruh Religiusitas, Motivasi Islam Terhadap Kinerja Karyawan PT. Dinamika Megatama Citra - Abida, Syafaatul; Nizar, Muhammad; Iltiham, Muhammad Fahmul (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2024)
This study aims to explore the relationship between Islamic religiosity and motivation with employee performance at PT. Dynamics of Megatama Citra. By looking at these factors from a holistic perspective, researchers seek to provide deeper insight into how spiritual and religious values can affect employee productivity levels and performance. This research uses a quantitative approach that involves the use of quantitative instruments and analytical methods. The analysis method used is the path analysis method, which allows researchers to analyze patterns of relationships among the variables under study. The results of testing using smart PLS show that Islamic religiousity has a significant influence and positive relationship with employee performance. So it can be concluded that when employees of PT. The dynamics of Megatama Citra has a high level of Islamic religiosity, which will affect the improvement of employee performance behavior.